Do not ask, but you shall still receive: Newcomer reactions to receiving negative gossip. (22nd April 2022) - Jalil, Daroon; Xu, Xiaohong; Jiang, Lixin; Wang, Hai‐Jiang
Abstract: As research regarding the targets and initiators of workplace gossip is gaining traction, one perspective that remains overlooked is the gossip receiver. Organizational newcomers are a particularly relevant population to study the impact of receiving negative gossip on because they use social information to navigate an unfamiliar organizational terrain. We propose a parallel moderated mediation model in which receiving negative gossip has contradicting effects on newcomer job anxiety through perceived social inclusion and negative rumination, and agreeableness as a boundary condition of the effects of receiving negative gossip. We collected data from 202 newcomers using a four‐wave time‐lagged design and found that receiving negative gossip increased newcomer job anxiety via negative rumination but did not decrease job anxiety via perceived social inclusion. Further, agreeableness moderated the effect of receiving negative gossip on negative rumination (but not perceived social inclusion) such that the effect of receiving negative gossip on negative rumination was stronger for less agreeable newcomers. Lastly, the indirect effect of receiving negative gossip on job anxiety via negative rumination was stronger for less agreeable newcomers. Theoretical and practical implications specific to gossip and newcomers are discussed.